A critical review of gain enhancement methods for microstrip antenna - Quzwain, Kamelia; Nabila, Haifa; Anwar, Radial; Ismail, Alyani (Bentham Science Publishers, 2023)
In the recent years, the development in communication system has grown rapidly, especially for the growth of broadband wireless technologies. This technology has some advantages, for instance, flexibility for the transmission of data with very high data rate communications. Antenna is one of the crucial components of broadband wireless systems because it has ability to emit and receive radio waves. There are various types of antennas and microstrip is one of the most popular designs nowadays. This antenna has some advantages and disadvantages. Low gain is known as one of the disadvantages of microstrip antenna. However, there are numerous methods which can be used to enhance gain. Some researches have been done by numerous researchers throughout the world in tackling this disadvantage. This paper presents a critical review of different methods employed to alleviate this problem. For ease of understanding, this paper is classified into five approaches: array configuration approaches, air substrate approaches, metamaterial approaches, yagiuda approaches, and other approaches.